Torsional fatigue resistance of pathfinding instruments manufactured from several nickel-titanium alloys - Alcalde, M. P.; Duarte, M. A. H.; Bramante, C. M.; Tanomaru-filho, M. [UNESP]; Vasconcelos, B. C.; So, M. V. R.; Vivan, R. R. (Wiley-Blackwell, 2018)
AimTo evaluate the torsional properties of pathfinding nickel-titanium (NiTi) rotary instruments manufactured from several NiTi alloys, ProGlider (M-wire), Hyflex GPF (conventional NiTi Wire and controlled memory wire), Logic (conventional NiTi wire and controlled memory wire) and Mtwo (conventional NiTi wire). MethodologyA total of 56 NiTi instruments from Glidepath rotary systems (n=8) were used: Logic (size 25, .01 taper), Logic CM (size 25, .01 taper), ProGlider (size 16, .02 taper), Hyflex GPF (size 15, .01 taper), Hyflex GPF CM (size 15, .02 taper; size 20, .02 taper) and Mtwo (size 10, .04 taper). The torsion tests were performed based on ISO 3630-1 (1992). Three millimetres of each instrument tip was clamped to a small load cell by a lever arm linked to the torsion axis. Data were analysed using a one-way analysis of variance (anova) and Tukey test with a significance level at a=5%. ResultsThe Logic size 25, .01 taper had significantly higher torsional strength values (P<0.05). The ProGlider was significantly different when compared with Hyflex GPF size 15, .01 taper and size 15, .02 taper (P<0.05). The Logic CM size 25, .01 taper had significantly higher torsional strength than Hyflex GPF size 15, .01 taper and size 15, .02 taper (P<0.05). No difference was found amongst Mtwo size 10, .04 taper and Hyflex GPF groups (size 15, .01 taper; size 15, .02 taper; size 20, .02 taper). In relation to the angle of rotation, Logic CM size 25, .01 taper and Hyflex GPF size 15, .01 taper had the highest angle values (P<0.05). The ProGlider had the lowest angle values in comparison with all the groups (P<0.05) followed by Mtwo size 10, .04 taper. The Logic size 25, .01 taper had significantly higher angle of rotation values than ProGlider and Mtwo size 10, .04 taper (P<0.05). ConclusionThe Logic size 25, .01 taper instrument made of conventional NiTi alloy had the highest torsional strength of all instruments tested. In addition, the ProGlider instrument manufactured from M-Wire alloy had the lowest angle of rotation to fracture in comparison with the other instruments.
Keywords: Nickel-Titanium; pathfinding instruments; rotary instruments; thermal treatment